2021
DOI: 10.47391/jpma.274
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors related to fast food consumption among Mutah University Students, Jordan

Abstract: Objective: To identify the prevalence and factors related to fast food consumption among Mutah University students in Jordan. Methods: A cross-sectional study was conducted during the period from January-April, 2019. A sample of 503 students was recruited from different faculties. The participants were interviewed using a structured and a validated questionnaire. Height and weight were measured for the Body Mass Index (BMI) calculation. Statistical analyses were performed using descriptive, t-test and correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…[ 32 ] Furthermore, our results agreed with a study reported that fast-food consumption was not linked to living in family or nonfamily households. [ 26 ] However, our results did not find a strong relationship between education level and odds of fast-food intake which disagreed with previous studies reported that the likelihood of fast-food consumption was increased with high education level, [ 27 ] or low education level. [ 33 ] The present study revealed an interesting observation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…[ 32 ] Furthermore, our results agreed with a study reported that fast-food consumption was not linked to living in family or nonfamily households. [ 26 ] However, our results did not find a strong relationship between education level and odds of fast-food intake which disagreed with previous studies reported that the likelihood of fast-food consumption was increased with high education level, [ 27 ] or low education level. [ 33 ] The present study revealed an interesting observation.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 25 ] A report from Jordan found that 59.4% of young adults takes fast-food twice weekly at least. [ 26 ] Weekly fast-food consumption was reported in 41% of Malaysian adults aged 24 to 49 years. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food consumption patterns in Jordan have not been studied at the population level. The published studies focused on specific age groups, such as food consumption among university students [33,34] and food and nutrient consumption in certain disease cases [35,36]. These studies used a food frequency questionnaire to focus on food group consumption, whereas 24-h DR was rarely used.…”
Section: Expected Findingsmentioning
confidence: 99%
“…In fact, college students are a vulnerable group that constantly faces a number of health challenges related to an unhealthy diet, characterized by a high intake of saturated fats, sodium, and free sugars ( Quiliche et al, 2021 ; Nuñez-Leyva et al, 2022 ). Several studies have reported unhealthy dietary practices among university students, including increased consumption of fast food and high-fat foods ( Chourdakis et al, 2011 ; Mwafi et al, 2021 ; Saha et al, 2021 ). One study found that university students had significantly higher average intakes of total fat, saturated fat, and dietary cholesterol and lower intakes of polyunsaturated and monounsaturated fats ( Chourdakis et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%